2023
DOI: 10.3390/ijms24087114
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD137+ T Cell Levels Are Correlated with Response to Pembrolizumab Treatment in Advanced Head and Neck Cancer Patients

Abstract: Pembrolizumab, an anti-PD-1 antibody, has been approved as first-line treatment for recurrent or metastatic head and neck squamous cell carcinoma ((R/M) HNSCC). However, only a minority of patients benefit from immunotherapy, which highlights the need to identify novel biomarkers to optimize treatment strategies. CD137+ T cells have been identified as tumour-specific T cells correlated with immunotherapy responses in several solid tumours. In this study, we investigated the role of circulating CD137+ T cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…In metastatic renal carcinoma, CD137 + T cells were associated with the clinical response to tyrosine kinase inhibitors [ 23 , 24 ]. We recently demonstrated that the amount of circulating CD137 + T cells had a predictive and prognostic role in survival in advanced head and neck squamous cell carcinoma (HNSCC) patients treated with pembrolizumab as first-line therapy [ 15 ]. In another study carried out on 109 patients with different solid tumors under anti-PD1 treatment, we demonstrated and validated that high levels of CD137 + T cells were a prognostic factor of PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In metastatic renal carcinoma, CD137 + T cells were associated with the clinical response to tyrosine kinase inhibitors [ 23 , 24 ]. We recently demonstrated that the amount of circulating CD137 + T cells had a predictive and prognostic role in survival in advanced head and neck squamous cell carcinoma (HNSCC) patients treated with pembrolizumab as first-line therapy [ 15 ]. In another study carried out on 109 patients with different solid tumors under anti-PD1 treatment, we demonstrated and validated that high levels of CD137 + T cells were a prognostic factor of PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of regulatory T cells (Tregs) to Lox1 + -PMN-MDSCs predicted the response in Nivolumab-treated NSCLC patients [ 13 ]. We recently demonstrated the predictive and prognostic role of CD137 + T cell subset in solid tumors, including NSCLC, under anti-PD1 treatment [ 14 , 15 ]. This population was recognized as naturally occurring antigen-specific T cells and was associated with the wellness of the immune system [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%